Malignant Peripheral Nerve Sheath Tumors in Children with Neurofibromatosis Type 1. (16th September 2014) - Pourtsidis, Apostolos; Doganis, Dimitrios; Baka, Margarita; Bouhoutsou, Despina; Varvoutsi, Maria; Synodinou, Maria; Giamarelou, Panagiota; Kosmidis, Helen
Abstract : Purpose . Malignant peripheral nerve sheath tumors (MPNSTs) are rare in children and account for approximately 5–10% of all soft tissue sarcomas in adults. MPNSTs may occur independently but individuals with neurofibromatosis type 1 (NF1) have a significantly increased risk. Our aim is to present patients with MPNST treated in our department. Cases and Results . In this report we present 4 cases of MPNSTs (3 females: 13, 12, and 13 years old and 1 male: 10 years old) arising in patients with NF1. All of them presented with an enlarging mass and pain at diagnosis. Tumor was located in the buttock, the spinal cord, the trunk, and the left leg proximal to the heel. Wide excision of the tumor and radiotherapy were applied to all and adjuvant chemotherapy was given to three of them after the disease was progressed. All four died 32, 18, 10, and 22 months after diagnosis with progressive disease locally and pulmonary metastases in two of them. Conclusions . In conclusion, MPNSTs arising in patients with NF1 are high grade sarcomas with short survival. Individuals with NF1 should be followed closely in order to identify early the development of MPNSTs. Aggressive surgery and complete excision significantly improves disease-free survival. The usefulness of radiation therapy in MPNSTs is not determined although all patients will receive radiation therapy at some stage of the disease. The role of chemotherapy is unclear.